Pengaruh model pembelajaran kooperatif Student Team Achievemen Division (STAD) dan Jigsaw terhadap minat dan hasil belajar bola basket pada siswa kelas XI SMA Negeri 1 Pecangaan - Maftukin Hudah; Chandra Febriyan Fitriawan (Jurnal Kualita Pendidikan, 2020)
The objectives of this study were: 1) To find out whether the Student Teams Achievement Division (STAD) learning model had an effect on student interest and learning outcomes in basketball material for class XI SMA Negeri 1 Pecangaan, 2) To determine whether the Jigsaw learning model had an effect on interests and outcomes. student learning on basketball material for class XI SMA Negeri 1 Pecangaan. This type of research is a quasi-experimental sample selection in the True Experimental Design type Pretest-Posttest Control Group Design with sample selection then given a pretest to determine the initial state whether there is a difference between the experimental group and the control group. Pretest results are good if the value of the experimental group is not significantly different. After that the experimental group received treatment, and the control group also received treatment. Then both of them get a posttest to find out the results of the treatment that has been done. The results of the study based on the calculation of the two-party t-test obtained t = 4.304. From the t distribution list with df = 39 + 38 - 2 = 75 and the real level of 5%, it is obtained t table = 1.992. Because t count > t table (4.304 > 1.992) then H0 is rejected and Ha is accepted, it can be concluded that the interest and learning outcomes of students using the STAD model are better than students using the Jigsaw model. But both of these models have an effect on basketball interest and learning outcomes. The suggestion that the writer can convey is that the Student Teams Achievement Division (STAD) and Jigsaw learning model can be used as an alternative for teachers in teaching.